STRATEGI KOMUNIKASI BADAN NARKOTIKA NASIONAL (BNN) DALAM MENGURANGI JUMLAH PENGGUNA NARKOBA DI KOTA PALU - Arief, Andi Mohammad (Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Tadulako, 2020)
The aim of this research is to look at BNN's communication strategy in the Dipa Program in reducing the number of drug users in Palu City by examining the problems in this research, namely (1) What is BNN's communication strategy in implementing the Dipa program in Palu City, (2) What are the factors? This is the only thing that hinders BNN in implementing the Dipa program in Palu City. Research objectives (1) To determine BNN's communication strategy in implementing the Dipa program in Palu City. (2) To find out the obstacles experienced by BNN in implementing the Dipa program in Palu City. This type of research uses a qualitative descriptive approach. Location: This research was conducted at the Palu City National Narcotics Agency Office located at Jalan Soekarno Hatta, Palu City. Data collection techniques include observation, interviews and documentation. The research uses qualitative data analysis techniques, namely data reduction, data presentation, and drawing conclusions. Based on the research results, it shows that the National Narcotics Agency (BNN) Communication Strategy in Reducing the Number of Drug Users in Palu City is by implementing DIPA program activities where the activities start from planning a structured communication strategy in implementing communication strategies in outreach/socialization activities which are generally aimed at in government agencies, educational agencies, the private sector and related community groups, in order to reap the results of the common goal of reducing the number of drug abuse in the city of Palu. Apart from that, looking at the obstacle factors related to human resources, in this case a group of people who are less likely to participate in fulfilling the invitation from BNN if they are not provided with transportation costs for them and lack of coordination from related parties.